Hydrological Data Banking for Sustainable Development in Nigeria: An Overview - Ocheri Maxwell (Graduate Program of Syiah Kuala University, 2013)
Abstract - This paper examines the importance of hydrological data banking for sustainable development in Nigeria. Water related projects have failed woefully in Nigeria because they are executed without recourse to or lack of relevant hydrological data. Hydrologists primarily are saddled with the responsibilities of data gathering, processing, storage and retrieval on all components of the hydrological cycle such as precipitation, evaporation, runoff, infiltration, stream flow to mention a few. This however can only be done when hydrologists are adequately trained and efficient hydrological gauging stations with up to date equipment are established. The current situation in Nigeria is that hydrological data banking is lacking which is linked with inadequate and inefficient guaging stations and trained manpower. There is the need to make hydrological data collection, processing, storage/retrieval and banking for sustainable development a must in Nigeria. Government and relevant agencies and institutions need to step up action in this wise. Keywords: Hydrology, water inventory, river, data banking